The relationship of biological factors to swimming performance in top Polish juniorswimmers aged 12 to 14 years - Kunski, H.; Jegier, A.; Maslankiewicz, A. (Swimming Science V, 1988)
Only a few reports are found in the literature that concern the relationship between progress in swimming performance and dynami.:s of change of chosen biological parameters. On examining prospectively some swimmers, Oelschlager (1969) indicated a close relationship between progress in sport competition and increase of heart size and physical efficiency. Keul, Lehmann, Dickhuth, and Berg (1980) observed a correlation similar to Oelschlager' s in males who specialized in running and swimming distances requiring performances of over 2 minutes duration. However, the progress of sport performances has been observed with a constant level of oxygen uptake in Polish senior (Kunski & Sztobryn-Rutkowska, 1982) and top Swedish swimmers (Eriksson, Holmer, & Lundin, 1978). As Martinosov, Bulgakova, Statkjawiczjenje, Filmonova, and Chebotarieva (1984) stated, the progress of sport performances in female swimmers at the ages of 11 to 16 is mainly related to an increase in the morphological and functional aspects of the organism. According to Bulgakova and Voroncov's (1978) view, the basis for anticipating a swimmer's performance should be stability of features, which do not change under the influence of training and are controlled by genetic factors, namely skeletal diameters, ankle flexibility, and the results of long-distance swimming. The main aim of this investigation was to find in what way changes in chosen biological parameters affect the progress of swimming performance in junior swimmers aged 12 to 14 years.